Workshop on Teaching Module Development on Merdeka Curriculum in Elementary, Junior High, and Senior High Schools, Toba District, Sanggau Regency - Dona Fitriawan; Hartoyo, Agung; Mirza, Ade; Yusmin, Edy; Siregar, Nurfadilah; R, Zubaidah; Yani T, Ahmad; Jamiah, Yulis; Lestari Pasaribu, Revi; Winarji, Agus; Novianti, Metia; Febriani Meldi, Nadya (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
The purpose of this workshop and mentoring program in general is to support government programs related to the Implementation of Merdeka Curriculum. The specific objectives are: 1) participants' understanding of the teaching modules in the independent curriculum; 2) participants' understanding of the profile of Pancasila students in the independent curriculum. This activity was carried out in the form of in service for 4 days, namely from Monday to Thursday, January 24 to 28, 2024. This activity was carried out in SD, SMP, SMA Toba Sanggau Regency. The outputs of this activity include softcopy and hardcopy of the results of service activities. Some supporting materials that need to be informed and discussed by participants as refresher material for those who have received from other sources, increase knowledge for those who do not have it, expand the horizons of knowledge for those who want to develop themselves. The materials are: Teaching Materials, Flow of Learning Objectives, Profile of Pancasila Students, Assessment, Follow-up Evaluation of Merdeka Curriculum. Participants in this service activity are all teachers involved in MGMP at the elementary, junior high, and high school levels in the Toba sub-district of Sanggau Regency. The number of teachers who participated in this activity from the beginning to the end of the activity amounted to approximately 100 MGMP teacher participants in Toba District, Ketapang Regency. The result of this service activity is the formation of a draft teaching material on the independent curriculum approved by MGMP in SD, SMP, SMA Toba, Sanggau Regency. Furthermore, the real result is the ease of access for teachers in managing teaching materials and the continuous collaboration between MGMP teachers in Toba sub-district and mathematics education lecturers at FKIP Tanjungpura University. The product obtained is a set of teaching materials on the independent curriculum suitable for school teachers and published in a publication article to an accredited national journal.